The Correlation Between Vlog-Based Learning and Students’ Speaking Motivation - Siti Faizah Salsabila Darin; Vika Nadhifatul Fikriyah; Annisa Afriyuni Setiawan; Nafan - Tarihoran (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the correlation between vlog-based learning and students’ speaking motivation among 100 students in an English Language Education Program using a quantitative correlational design. Data were collected through validated Likert-scale instruments measuring vlog engagement and speaking motivation. Pearson’s correlation analysis revealed a strong, significant positive relationship (r = 0.6462, p 0.001), with vlog engagement explaining 41.76% of the variance in motivation. Descriptive results showed above-average levels of both vlog engagement and speaking motivation. While intrinsic motivation and aspirations were high, behavioral aspects such as confidence and participation were relatively lower, indicating a gap between intention and action. Overall, vlog-based learning is a promising strategy to enhance speaking motivation in EFL contexts.